2020
DOI: 10.1007/s11042-020-09425-0
|View full text |Cite
|
Sign up to set email alerts
|

Human segmentation in surveillance video with deep learning

Abstract: Advanced intelligent surveillance systems are able to automatically analyze video of surveillance data without human intervention. These systems allow high accuracy of human activity recognition and then a high-level activity evaluation. To provide such features, an intelligent surveillance system requires a background subtraction scheme for human segmentation that captures a sequence of images containing moving humans from the reference background image. This paper proposes an alternative approach for human s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 61 publications
0
26
0
1
Order By: Relevance
“…Societal impacts. Image segmentation has several applications, including autonomous driving [1], medical image analysis [3], and video surveillance [2]. Although we have not focused on any specific application in this work, we describe some potential societal impacts in regard to image segmentation in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Societal impacts. Image segmentation has several applications, including autonomous driving [1], medical image analysis [3], and video surveillance [2]. Although we have not focused on any specific application in this work, we describe some potential societal impacts in regard to image segmentation in general.…”
Section: Discussionmentioning
confidence: 99%
“…The great advancements of deep learning methods in recent years have had a large impact on many computer vision tasks, with no exception for semantic segmentation. The ability to automatically segment images has been found useful in many applications, including autonomous driving [1], video surveillance [2], and medical image analysis [3]. Fully-supervised segmentation frameworks have achieved remarkable results by utilizing large datasets of pixel-wise annotated images.…”
Section: Introductionmentioning
confidence: 99%
“…They have segmented the person from the background on a video using a global background attenuation model. Monica Gruosso et al [8] showed the possibility of automatic human recognition and segmentation in a surveillance video system. The authors used SegNet [49] encoder-decoder Convolution Neural Network (NCNN) model for the experiment.…”
Section: Image Segmentation In Videomentioning
confidence: 99%
“…Recently, human action recognition has attracted wide attention [10,44] because of its applications, such as automated surveillance [1], intelligent robots [23], and behavior monitoring in homes [3,15,16,46,60]. Several sensors, such as cameras [60], electromagnetic waves [31], and wearable devices [2,8,47,55,66], have been employed to detect human activities.…”
Section: Introductionmentioning
confidence: 99%